Local Perspective: Factors Associated with Covid-19 Preventive Behavior in West Nusa Tenggara, Indonesia - Artha Budi Susila Duarsa; Aena Mardiah; Fachrudi Hanafi; Dany Karmila; Ayu Anulus (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: The case fatality rate (CFR) of Covid-19 deaths in Indonesia on June 16, 2020 was 5.52% and 4.19% in West Nusa Tenggara. One of the causes of this high percentage of deaths is the lack of preventive behavior against Covid-19. This study aims to analyze factors associated with Covid-19 preventive behavior among people in West Nusa Tenggara, Indonesia.Subjects and Method: A cross-sectional study was conducted in 10 cities/districts in West Nusa Tenggara from May-June 2020. A total of 385 people were enrolled in this study. Data were collected using a questionnaire distributed in the form of Google form and analyzed using multiple linear regressions with Stata 13.Results: High education level (≥high school) (aOR= 0.43; 95%CI=0.03 to 0.82; p=0.033), perceived benefits (aOR=0.16; 95%CI= 0.07 to 0.25; p=0.001), and good knowledge (aOR=0.19; 95%CI= 0.01 to 0.37; p=0.034) were increased the preventive behavior. While, male (aOR= 0.54; 95% CI= -0.89 to -0.19; p=0.002), perceived barriers (aOR= -0.16; 95%CI= -0.25 to -0.07; p= 0.001) were decreased the preventive behavior toward Covid-19, and they were statistically significant.Conclusion: Education higher than high school, high perceived benefit, and good knowledge are increase the local people behavior to prevent Covid-19 in West Nusa Tenggara.Keywords: Covid-19, preventive behavior, West Nusa TenggaraCorrespondence: Artha Budi Susila Duarsa. Faculty of Medicine, Universitas Islam Al-Azhar, Mataram. Unizar-Street Number 20, Turida, Sandubaya, Mataram, West Nusa Tenggara. Email: duarsaartha@unizar.ac.id. Mobile Phone: +62 812-9125-5000.Journal of Health Promotion and Behavior (2021), 06(01): 1-8https://doi.org/10.26911/thejhpb.2021.06.01.01